Average wage, qualification of the workforce and export performance in German enterprises: Evidence from KombiFiD data - Joachim Wagner (Institute for the Study of Labor (IZA), 2012)
Empirical investigations with enterprise level data from official statistics often use the average wage as a proxy variable for the qualification of the workforce, mostly due to the lack of detailed information on the qualification of the employees. This paper uses unique newly available data for German enterprises from the KombiFiD project that for the first time combine information from the statistics of employees covered by social security and information from surveys performed by the Statistical Offices to look at the quality of this proxy variable by investigating the link between the average wage in a firm and the qualification of the workforce. Furthermore, it demonstrates that detailed information on the qualification of the workforce sheds new light on the role of highly qualified employees for success on export markets that is not revealed by the average wage as a proxy variable. Based on the results of this paper it is argued that combined firm level data that stem from different data producers should be widely accessible for research.
urn:nbn:de:101:1-201203064042
Keywords: C81; F14; J31; 330; qualification of workforce; average wage; export; firm level data; Qualifikation; Arbeitskräfte; Lohnstruktur; Außenhandelswirtschaft; Exportindustrie; Schätzung; Deutschland